Pengembangan Media Pembelajaran Boneka Tangan Mata Pelajaran Bahasa Indonesia Materi Menyimak Dongeng Pada Siswa Kelas II Sekolah Dasar - Krisanti, Rosaria Yulinda; Suprihatien, Suprihatien; Suryarini, Diah Yovita (Trapsila: Jurnal Pendidikan Dasar, 2020)
AbstractThe lack of teaching effectiveness in teaching learning activity made students felt bored easily and noisy in the classroom. To resolve that problem needed teaching media used in learning process, one of them was puppet that developed as learning media completed with the stage to show the location of the story. This medium was used for understanding fairy tale material to intermediate grade 2. This writing used the development of Addie model (analysis, design, development, implementation, and evaluation). According to this unable condition to do a research, so this research ended in validity step as a measurement of worthiness using puppet medium for understanding fairy tale material. The worthiness of the validity media result was 94%, whereas validity material result in the first validator was 88,3% and the second was 86,6%. According to that validity result, we could conclude that teaching media using puppet could be used for understanding fairy tail material for intermediate grade 2.Â Keywords: media development of hand puppets, Indonesian language learning, listening to fairy tales.